L'analyse des politiques agricoles 2 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Au sommaire du rapport annuel 1997 du CTA, l'analyse des politiques agricoles